al-Ulama al-Indonesiun fi Dirasah al-Hadits al-Mu'ashirah - Ade Pahrudin (UIN Kiai Haji Achmad Siddiq Jember, 2021)
Ramadan is the ninth month of the Hijri month. A month in which the Qur’an was revealed, forgiveness and mercy, so there are many scholars throughout the Islamic world recently and in the past who are interested in this month. One of them is Indonesian Islamic scholar, Syaikh Taufiq Hakim. He wrote a book called